The Concept of Successor Heirs as a Contemporary Ijtihād in the Perspective of Ulama Dayah in Woyla District - Muhammad Husnul; Djawas, Mursyid; Shabarullah, Shabarullah; Maghfirah, Maghfirah (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2025)
The Compilation of Islamic Law (KHI), Article 185, in Indonesia recognizes the concept of a successor heir. In contrast, traditional fiqh holds that the right to inheritance is lost if the prospective heir dies before the decedent. Meanwhile, ulama dayah in Woyla District continue to adhere to classical fiqh texts and have not adopted the KHI’s provisions regarding successor heirs. This study aims to examine the views of ulama dayah in Woyla District on the concept of successor heirs and to analyze the concept from the perspective of Islamic law. The research employs a field study methodology with a juridical-normative-empirical approach. Data were collected through observation, interviews, and documentation, and were analyzed descriptively. The findings reveal that ulama dayah in Woyla District are unfamiliar with the concept of successor heirs as found in classical faraidh (Islamic inheritance law) literature. A paternal grandson may inherit in place of his deceased father if there are no other sons, whereas a maternal grandson cannot replace his deceased mother in the line of inheritance (patah titi). Furthermore, Islamic law, as reflected in the Qur’an, hadith, and sunnah, does not acknowledge the concept of successor heirs. In contrast, the Compilation of Islamic Law does recognize such a concept. These findings indicate a fundamental difference between the views of the ulama dayah in Woyla and the provisions of the KHI, particularly regarding the position of grandsons in inheritance matters.